Anti-IFI16 antibodies in scleroderma are associated with digital gangrene - McMahan, Zsuzsanna H. (Arthritis Rheumatol, 2016)
OBJECTIVE: Our aim was to examine the association between anti-interferon inducible protein 16 (IFI16) antibodies and clinical features of scleroderma. METHODS: Sera from a discovery sample of 94 scleroderma patients and 47 healthy controls were assayed for anti-IFI16 antibodies by ELISA, and associations were examined using regression analyses. As anti-IFI16 autoantibodies strongly associated with digital gangrene in the discovery sample, a subsequent 1:1 disease-duration matched case-control study was designed for further exploration. Cases were patients with scleroderma and digital gangrene, while controls had scleroderma and Raynaud’s alone (n=39 pairs). Nonparametric unadjusted matched-pair analyses, univariate and multivariable conditional logistic regression were performed. RESULTS: Anti-IFI16 antibodies in the discovery sample were more prevalent in scleroderma than controls (18% vs. 2%; p=0.01). Patients with anti-IFI16 antibodies were more likely to have limited scleroderma (77% vs. 46%; p=0.03), longer disease duration (15.2 [10.6–18.3] vs. 6.0 [3.4–13.8] years; p <0.01), digital gangrene (24% vs. 4%; p=0.02), and a low DLCO (p <0.01). In the case-control study, 35/78 (45%) were anti-IFI16 positive. Anti-IFI16 antibody levels were significantly higher in cases than matched controls (p=0.02). Adjusted for age, cutaneous subtype, smoking, and DLCO, high anti-IFI16 antibody levels associated with digital gangrene (adjusted OR 2.3; 95% CI 1.0, 5.6; p = 0.05). The odds of digital gangrene increased with higher antibody titers in a dose dependent manner. CONCLUSION: Anti-IFI16 antibodies are associated with digital gangrene in scleroderma. Longitudinal prospective studies exploring anti-IFI16 antibodies as a disease biomarker, and biological studies investigating the pathogenicity of these antibodies, are warranted.